ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT PT ABC - Gita Rose Aphrodita (Feedforward: Journal of Human Resource, 2023)
This study aims to determine the effect of a positive relationship between Organizational Culture and Job Satisfaction on Organizational Citizenship Behavior through Organizational Commitment as an Intervening Variable for employees of PT ABC, Jakarta. The method used in this study is a quantitative method, where data collection is through a questionnaire process that is given online. The data collection technique uses a non-probability sampling technique, where the respondents are permanent employees who have worked for two years at PT ABC, Jakarta. The sample size for collecting questionnaire data was given to 76 respondents. Statistical data analysis is Structural Equation Modeling where data processing uses PLS software. Results, Organizational Culture has a positive effect on Organizational Commitment, Job Satisfaction has a positive effect on Organizational Commitment, Organizational Commitment has a positive effect on Organizational Citizenship Behavior, Organizational Culture has not had a positive effect on Organizational Citizenship Behavior, Organizational Culture has not had a positive effect on Organizational Citizenship Behavior through the mediation of Organizational Commitment, Job Satisfaction does not positively influence Organizational Citizenship Behavior and Job Satisfaction positively influences Organizational Citizenship Behavior through the mediation of Organizational Commitment.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh hubungan positif antara Budaya Organisasi dan Kepuasan Kerja terhadap Organizational Citizenship Behavior melalui Komitmen Organisasional sebagai Variabel Intervening terhadap  karyawan PT ABC, Jakarta. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif, di mana pengumpulan data melalui proses kuesioner yang diberikan secara online. Teknik pengambilan data menggunakan teknik non – probability sampling, di mana responden karyawan tetap yang telah bekerja selama dua tahun pada PT ABC, Jakarta. Jumlah sampel untuk pengumpulan data kuesioner diberikan kepada 76 responden. Analisis data statistik adalah Structural Equation Modelling di mana pengolahan data menggunakan software PLS. Hasil, Budaya Organisasi memengaruhi secara positif terhadap Komitmen Organisasional, Kepuasan Kerja memengaruhi secara positif terhadap Komitmen Organisasional, Komitmen Organisaional memengaruhi secara positif terhadap Organizational Citizenship Behavior, Budaya Organisasi tidak memengaruhi secara positif terhadap Organizational Citizenship Behavior, Budaya Organisasi tidak memengaruhi secara positif terhadap Organizational Citizenship Behavior melalui mediasi Komitmen Organisasional, Kepuasan Kerja tidak memengaruhi secara positif terhadap Organizational Citizenship Behavior dan Kepuasan Kerja memengaruhi secara positif terhadap Organizational Citizenship Behavior melalui mediasi Komitmen Organisasional.